2016
DOI: 10.1111/jmcb.12306
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Ownership and Market Power in Banking: Evidence from a World Sample

Abstract: Ownership and competition in the banking sector are policy concerns around the world that are rarely comprehensively examined. For 131 countries and 13 years we match bank ownership with over 50,000 bank-year estimates of individual bank market power. At the individual bank level, ownership does not explain market power. At the country level, on the other hand, foreign bank ownership has a positive and significant impact on bank market power because foreign banks enter through mergers or acquisitions and not t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 97 publications
1
35
0
1
Order By: Relevance
“…Finally, following Delis et al. (), we test for potential non‐linear effects between competition, EALER, and risk. We did not find any evidence of such a linear effect…”
Section: Discussion Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, following Delis et al. (), we test for potential non‐linear effects between competition, EALER, and risk. We did not find any evidence of such a linear effect…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…For recent applications of Love and Zicchino ()’s model to the banking sector see e.g. Delis, Hasan, and Kazakis (), Head et al., (); Imbierowicz and Rauch ().…”
mentioning
confidence: 99%
“…A popular approach has been to estimate a translog cost function and take its derivative to obtain the marginal cost. Some recent work has shown that it is possible to improve on this methodology with semiparametric or nonparametric methods that allow for more flexibility in the functional form (Delis, Iosifidi, and Tsionas, 2013;Delis, Kokas, and Ongena, 2015). As we follow the exact same approach as in Delis, Kokas, and…”
Section: Measures Of Bank Market Powermentioning
confidence: 99%
“…The variable z, which is the so-called smoothing parameter, is crucial for the identification of the model and must be a variable that is highly correlated with a 2 and considerably varies by bank-year. Delis, Kokas, and Ongena (2015) propose using , which is intuitive given the high potential correlation of input prices with the output elasticity of costs. We use the same approach and we also verify that using each input price separately yields similar results.…”
Section: Appendix a Estimation Of Marginal Costmentioning
confidence: 99%
See 1 more Smart Citation